Morphological and phylogenetic analyzes reveal two new species of Melanconiella from Fujian Province, China - Mu, Taichang; Chen, Jinhui; Zhao, Zhiying; Zhang, Weibin; Stephenson, Steven L.; Yang, Chenjie; Zhu, Mengjia; Su, Hailan; Liu, Pu; Guan, Xiayu; Qiu, Junzhi (Frontiers in Microbiology, 2023)
Species of Melanconiella are plant pathogens and endophytic fungi. Many members of the genus Melanconiella have been frequently collected from the family Betulaceae (birches) in Europe and North America. During this study, four strains and two new species of Melanconiella were isolated from diseased leaves of Loropetalum chinense and Camellia sinensis in Fujian Province, China. Based on morphology and a multi-gene phylogeny of theinternal transcribed spacer regions with the intervening 5.8S nrRNA gene (ITS), the partial large subunit nrRNA gene (LSU), the second largest subunit of RNA polymerase II (RPB2), and the translation elongation factor 1-α gene (TEF1-α), Melanconiella loropetali sp. nov. and Melanconiella camelliae sp. nov. were identified and are described herein. Detailed descriptions, illustrations, and a key to the known species of Melanconiella are provided.